Efektivitas Supervisi Kepala Sekolah Dalam Peningkatan Profesionalisme Guru IPS di SMP 16 Seluma - Nur indah tiara; Bela efelyah; Desy Eka Citra Dewi (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Supervision services are provided to schools for the purpose of improving curriculum, learning, and instruction. As a logical consequence of this activity, schools must always be ready to be supervised because the purpose of supervision is clear. Educational problems are easily resolved if schools and principals understand the role and function of supervision. The aim of this research is to find out how effective the principal's supervision is in increasing the professionalism of social science teachers at SMP Negeri 16 Seluma. This research uses qualitative methods, and the respondents consist of school principals, social studies teachers and students. Observation, documentation, and interviews are data collection methods. The results of this research are as follows: 1) The ability of the principal to supervise social studies teachers at SMP Negeri 16 Seluma Regency. The principal must form a supervision team to start the supervision program; working with teachers to improve their competence as teachers; using direct and indirect approaches; and implementing methods, including meetings between principals and teachers. The school principal's professionalism supervision activities to increase the professionalism of social science teachers at SMP Negeri 16 Seluma were quite effective, with an average score of 3.83 and the professionalism of social studies teachers with an average score of 3.31.